Handheld computers in medicine: the way forward. Issue 957 (5th July 2005) - Horsley, A; Forster, L
Abstract : Handheld computers are now a common sight in medicine, but there are scarce data on who actually uses them and what functions are found to be most useful. This is the first study of handheld computer use in a British hospital, and shows that there is already considerable use and acceptance of the technology, with 22 of 55 (40%) physicians possessing and using such a device. Doctors in training grades are more likely to make use of medical software, particularly textbooks, calculators, and formularies. The main barriers to greater use of this technology were cost of software and poor applicability to UK practice.